Determinants of Business Freedom in Developing Countries: The Role of Institutional Development and Policy Mix - Audi, Marc; Poulin, Marc; Ali, Amjad (International Journal of Economics and Financial Issues, 2024)
Smooth and stable commercial/business activities are the prime concern of every nation, as these activities decide the developmental routes of the economy. This study has examined the role of institutional development and policy mix in determining business freedom in developing countries. Institutional development has been measured with the help of government effectiveness and political stability. Policy mix have been measured with the help of monetary freedom and fiscal freedom. To examine the impact of explanatory variables on the explained variable, this study has used panel least squares, random effect model, and generalized method of moments. The estimated results show that fiscal freedom has a negative and significant impact on business freedom, whereas, monetary freedom has an insignificant impact on business freedom in the case of developing countries. The results show that government effectiveness, political stability, and tread freedom are encouraging business freedom in developing countries. The corporate tax has a negative and significant impact on business freedom. Empirical show that developing countries are more inclined towards non-developmental expenditures, thus to control the negative impacts of fiscal freedom developing countries needs rationalization in government expenditures. Developing countries should promote government effectiveness, political stability, and trade freedom to enhance business freedom. To control the negative impacts of corporate taxes, developing countries should rationalize tax policies to promote business freedom.